Intervención de enfermería en la infección crónica de las vías respiratorias inferiores en un niño con parálisis cerebral infantil y epilepsia - Pinta Tuitise, Cinthya Jacqueline (2024)
Chronic lower respiratory tract infections (CLRTIs) are a common and serious problem in children with infantile cerebral palsy (CP) and epilepsy. Nursing intervention plays a crucial role in the management of these infections, as it can help prevent infection, promote recovery, and improve the patient's quality of life. We present the case of a 2-year-old boy aged 2 years and 7 months with diagnoses of PCI, epilepsy and severe chronic malnutrition. The main purpose of this study is to analyze nursing intervention for the management of chronic lower respiratory tract infection in a child with infantile cerebral palsy and epilepsy, to improve care and his quality of life. Based on Marjorie Gordon's functional patterns, altered patterns were detected, specifically the perception-health management, nutritional-metabolic, and activity-exercise patterns. A nursing care plan is developed using NANDA, NOC and NIC taxonomy, focusing on ineffective thermoregulation, ineffective airway clearance, nutritional imbalance and impaired physical mobility. We conclude that individualized, evidence-based nursing interventions is critical to the effective management of ICVRI in children with PCI and epilepsy. A holistic approach that addresses the patient's physical, psychosocial, and environmental needs can improve their quality of life and reduce the risk of complications.